Environmental remediation of sulfidic tailings with froth flotation: Reducing the consumption of additional resources by optimization of conditioning parameters and water recycling. (15th April 2019) - Nuorivaara, Ted; Björkqvist, Anna; Bacher, John; Serna-Guerrero, Rodrigo
Abstract: The removal of sulfidic species in tailings using froth flotation is a promising approach to prevent phenomena such as acid mine drainage. However, flotation requires the consumption of reagents and water that represent additional expenses. Despite the strong interest of scientists and industry alike on tailings remediation, there is no study on the minimization of resource consumption to promote the implementation of desulfurization with froth flotation. Following a systematic analysis based on Design of Experiments (DoE), this work aims to determine the implications of a decrease in the consumption of flotation reagents and fresh water. It was found that: i) recovery of sulfidic species is strongly influenced by collector concentration and the use of a preliminary re-dispersion step; ii) higher frother concentrations have a negative impact on sulfur grade in the concentrate; and iii) the interactions between the conditioning variables hereby explored have no significant impact on flotation performance. Composition analysis showed that flotation further aids in the removal of hazardous species, such as As, Co and Zn. Finally, the use of recycled water appears possible since flotation performance remained unchanged over 10 flotation cycles, despite the observed accumulation of metallic ions and organic species in the process water. Graphical abstract: Image 1 Highlights: Froth flotation offers attractive features for desulfurization of mineral tailings. A Design of Experiments was used to quantify the impact of conditioning parameters. Collector concentration and pre-dispersion have the strongest influence on sulfur recovery. It is demonstrated that flotation of sulfidic tailings is possible using recycled process water.